Small Mammals - Mohd Azlan, Jayasilan; Sally, Soo Kaicheen; Lok, Lisa Choy Hong; Khan, Faisal A.A. (UNIMAS Publisher and Wilmar Plantations Sdn Bhd, 2023)
The Bornean tropical rainforests harbour some of the most remarkable diversity of flora and fauna in the world (Jennings et al., 2015; Sodhi et al., 2004). Tropical biodiversity is highly threatened by land conversion for agricultural purposes. This calls for greater conservational prioritization (Wilcove & Koh, 2010; Fitzherbert et al., 2008) as many have become fragmented and disconnected. There are a total of 247 species of mammals recorded in Borneo, and small mammals make up approximately 81%, which can be sub-categorized into bats, shrews, treeshrews, rats, mice, squirrels and flying squirrels (Phillipps & Phillipps, 2016). Borneo is regarded as one of the biodiversity hotspots, sustaining a high concentration of endemism, including approximately 19% of mammals (5% of the 99 bats species and 26 Rodentia), 20% of snakes and 6% of birds (Mohd-Azlan & Lawes, 2011). S